Linking global trade and human rights : new policy space in hard economic times - Drache, Daniel, 1941-; Jacobs, Lesley A. (New York, NY : Cambridge University Press, 2014)
'The concept of policy space is critical to understanding the impact of globalization on public policy in the twenty-first century. For the purposes of this book, a policy space is an arena where national governments have the freedom and capacity to design and implement public policies of their own choosing (Grindle & Thomas, 1991; Koivusalo et. al., 2010). In market economies, policy spaces reflect the insight that certain realms of public life should be governed by collective decision making designed to advance the public interest whereas in other realms markets reign (Drache, 2001). The spatial metaphor expresses, in other words, the claim that there are certain sites where government action has legitimacy. Ultimately, national policy spaces matter because they provide opportunities for governments to be innovative in the development of public policy on these sites, especially in terms of advancing social justice goals (Jacobs, 2004). The unifying theme of this book is that there are major reconfigurations of social and economic policy spaces for national governments on the international landscape during the hard economic times that follow global financial crises. After the 2008 financial crisis, state action extended into new areas and was being deployed in new and innovative ways from the Cash for Clunkers program in the US to successful anti-poverty programs in Brazil. In India the national Rural Employment Scheme to guarantee a minimum number of paid hours annually to hundreds of millions of its poorest is the largest social welfare scheme in the world'--
Introduction / Daniel Drache and Lesley Jacobs -- Humanising global economic governance / Sol Picciotto -- The promise of linking human rights and trade / Ernest-Ulrich Petersmann -- Free trade agreements and global policy space after the great recession / Jorge Heine and Joseph Turcott -- From Seattle to Occupy: the shifting focus of social protest / Tomer Broude -- What's next for global labour? : power dynamics and industrial relations systems in a hyperglobalized world / Daniel Drache -- Global tobacco control and trade liberalization : new policy spaces? / Lesley Jacobs -- Business, policy spaces, and governance in India / Kuldeep Mathur -- India's pharmaceutical industry : policy space that fosters technological capability / Amit Ray and Saradindu Bhaduri -- Reducing poverty in Brazil : finding policy space for meeting developmental needs / Kathryn Hochstetler -- The global health policy agenda and shrinking policy spaces in the post crisis landscape / Ron Labonte -- The World Trade Organization and food security after the global food crises / Matias Margulis -- Decent work for domestic workers as a new policy space / Adelle Blackett -- Is there policy space for human rights linkages in China's trade and investment strategy? / Ljiljana Biukovic -- Human rights and social justice in China / Pitman Potter -- New policy space for collective bargaining in China / Sarah Biddulph -- Industrial relations in post-transition China : the challenges of inequality and social conflict / Chang-Hee Lee.
'This book has its origins in a major international workshop held at York University in Toronto in October 2011'--Acknowledgements.
Includes bibliographical references and index.
Keywords: Foreign trade regulation -- Congresses; Human rights -- Congresses; Law and economic development -- Congresses; Law and globalization -- Congresses